Physical ability, cervical function, and walking plantar pressure in frail and pre-frail older adults: An attentional focus approach - Pinloche, Laurianne; Zhang, Qingshan; Berthouze, Sophie E.; Monteil, Karine; Hautier, Christophe (Frontiers in Aging, 2022)
Aging and increased vulnerability define the clinical condition of frailty. However, while the cervical function is recognized as a determinant of balance and walking performance, no study simultaneously physical ability, cervical function, balance, and plantar pressure distribution in walking in nursing house population. Thus, the present study aimed to compare these parameters between Frail and Pre-Frail aged people. Thirty-one (12 men and 19 women) institutionalized participants (age: 89.45 ± 5.27 years, weight: 61.54 ± 9.99 kg, height: 160,34 ± 7,93 cm) were recruited and divided into Pre-Frail and Frail groups according to SPPB (Short Physical Performance Battery) score (Frail < 6, Pre–Frail ≥ 6). Participants performed the Timed Up and Go Test (TUGT) and a static balance evaluation. The cervical range of motion (COM), knee extensor strength, and walking plantar pressure distribution have been measured. The Pre-Frail group showed a higher gait speed (ES = 0.78, p≤0.001) and a better TUGT, as well as higher knee extensor strength (ES = 0.4, p = 0.04). Furthermore, the Pre-Frail group presented a center of pressure (COP) displacement velocity on the sagittal axis (ES = 0.43, p = 0.02) and a more COP projection on this axis (ES = 0.43, p = 0.02). No significant difference has been observed between the two groups concerning the total contact time and most of the plantar pressure parameters except for the rear foot relative contact time which was lower in the Pre-Frail group. The Pre-Frail group also showed better cervical tilt mobility (ES = 0.35, p=0.04). This study highlights the influence of some new parameters on frailty in older people, such as cervical mobility and plantar pressure distribution in walking.